2016
DOI: 10.7717/peerj.2509
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in pacing during ‘Ultraman Hawaii’

Abstract: BackgroundTo date, little is known for pacing in ultra-endurance athletes competing in a non-stop event and in a multi-stage event, and especially, about pacing in a multi-stage event with different disciplines during the stages. Therefore, the aim of the present study was to examine the effect of age, sex and calendar year on triathlon performance and variation of performance by events (i.e., swimming, cycling 1, cycling 2 and running) in ‘Ultraman Hawaii’ held between 1983 and 2015.MethodsWithin each sex, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 41 publications
(54 reference statements)
3
15
0
Order By: Relevance
“…Second, the findings of the present research provide insight into the sociodemographic characteristics of the non-finishers, who were predominantly male and of high socioeconomic status, similarly to the finishers. These results are in line with previous studies reporting that ultra-trailers generally tend to have high socioeconomic status and to be well-educated [ 72 ] and predominantly male (e.g., [ 73 , 74 ]). From a descriptive point of view, the socioeconomic status does not seem to play a role in dropout.…”
Section: Discussionsupporting
confidence: 92%
“…Second, the findings of the present research provide insight into the sociodemographic characteristics of the non-finishers, who were predominantly male and of high socioeconomic status, similarly to the finishers. These results are in line with previous studies reporting that ultra-trailers generally tend to have high socioeconomic status and to be well-educated [ 72 ] and predominantly male (e.g., [ 73 , 74 ]). From a descriptive point of view, the socioeconomic status does not seem to play a role in dropout.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding pacing, women have shown to be better pacers with a more even pace throughout a race [ 17 , 22 , 23 ]. This effect could also be shown in two studies on ultra-triathlons [ 24 , 25 ] and one on a 100-km marathon [ 22 ]. However, to our knowledge, there has not yet been a publication observing the correlation between sex and pacing in an ultramarathon with such great elevation gain as the UTMB ® .…”
Section: Introductionmentioning
confidence: 56%
“…It has been shown that performance in the 'Ironman Hawaii' varied by nationality with the fastest women originating from the USA, UK and Switzerland and the fastest men from USA, Germany and Australia (1). It has been also found that pacing in the 'Ultraman Hawaii' varied by performance level (8).…”
Section: Introductionmentioning
confidence: 93%